Comparing Experimental Measurements of Limiting Current in Polymer Electrolytes with Theoretical Predictions. Issue 14 (24th September 2019) - Gribble, Daniel A.; Frenck, Louise; Shah, Deep B.; Maslyn, Jacqueline A.; Loo, Whitney S.; Mongcopa, Katrina Irene S.; Pesko, Danielle M.; Balsara, Nitash P.
Abstract : The limiting current is an important transport property of an electrolyte as it provides an upper bound on how fast a cell can be charged or discharged. We have measured the limiting current in lithium-lithium symmetric cells with a standard polymer electrolyte, a mixture of poly(ethylene oxide) and lithium bis(trifluoromethane) sulfonamide salt at 90°C. The cells were polarized with increasing current density. The steady-state cell potential was a smooth function of current density until the limiting current was exceeded. An abrupt increase in cell potential was taken as an experimental signature of the limiting current. The electrolyte mixture was fully characterized using electrochemical methods to determine the conductivity, salt diffusion coefficient, cation transference number, and thermodynamic factor as a function of salt concentration. We used Newman's concentrated solution theory to predict both cell potential and salt concentration profiles as functions of position in the cell at the experimentally applied current density. The theoretical limiting current was taken to be the current at which the calculated salt concentration at the cathode was zero. We see quantitative agreement between experimental measurements and theoretical predictions for the limiting current. This agreement is obtained without resorting to any adjustable parameters.